Physical activity level measured by accelerometry and physical fitness of schoolchildren - Estivaleti,José Matheus Oliveira (2023)
Abstract Objective: To describe and compare physical fitness variables according to compliance with the recommendations of physical activity, measured by accelerometry. Methods: The sample gathered 120 students, 57 boys and 63 girls aged 9 to 11 years. The variables analyzed were: weight, stature, BMI, skinfolds, waist circumference, agility, flexibility, speed and strength of upper and lower limbs, and abdominal strength. Physical activity was measured objectively using an accelerometer. The students were divided into two groups: “complies with recommendations” (≥60min/day) and “does not comply with recommendations” (<60min/day). To verify the normality of the data, the Kolmogorov-Smirnov test was used. The mean values of students who do or do not comply with the physical activity recommendation were compared using Student's t and U-Mann Whitney tests. The level of significance was set at p<0.05. Results: The students who followed the recommendation showed significantly lower values compared to those who did not for adiposity (sum of 7 skinfolds); body weight; body mass index (BMI) and abdominal strength. No significant differences were found in the variables of speed and agility, and the upper limbs’ strength was greater in subjects who did not comply with recommendations. Conclusions: Students who complied with physical activity recommendations had better body composition and more abdominal strength than those who did not.